Characterization of the Rac-GAP (Rac-GTPase-activating protein) activity of beta2-chimaerin, a 'non-protein kinase C' phorbol ester receptor. - Caloca, Maria Jose (2003)
The regulation and function of beta2-chimaerin, a novel receptor for the phorbol ester tumour promoters and the second messenger DAG (diacylglycerol), is largely unknown. As with PKC (protein kinase C) isoenzymes, phorbol esters bind to beta2-chimaerin with high affinity and promote its subcellular distribution. beta2-Chimaerin has GAP (GTPase-activating protein) activity for the small GTP-binding protein Rac1, but for not Cdc42 or RhoA. We show that acidic phospholipids enhanced its catalytic activity markedly in vitro, but the phorbol ester PMA had no effect. beta2-Chimaerin and other chimaerin isoforms decreased cellular levels of Rac-GTP markedly in COS-1 cells and impaired GTP loading on to Rac upon EGF (epidermal growth factor) receptor stimulation. Deletional and mutagenesis analysis determined that the beta2-chimaerin GAP domain is essential for this effect. Interestingly, PMA has a dual effect on Rac-GTP levels in COS-1 cells. PMA increased Rac-GTP levels in the absence of a PKC inhibitor, whereas under conditions in which PKC activity is inhibited, PMA markedly decreased Rac-GTP levels and potentiated the effect of beta2-chimaerin. Chimaerin isoforms co-localize at the plasma membrane with active Rac, and these results were substantiated by co-immunoprecipitation assays. In summary, the novel phorbol ester receptor beta2-chimaerin regulates the activity of the Rac GTPase through its GAP domain, leading to Rac inactivation. These results strongly emphasize the high complexity of DAG signalling due to the activation of PKC-independent pathways, and cast doubts regarding the selectivity of phorbol esters and DAG analogues as selective PKC activators.